Parametric control of Meissner screening in light-driven superconductors. (1st November 2022) - Homann, Guido; Cosme, Jayson G; Mathey, Ludwig
Abstract: We investigate the Meissner effect in a parametrically driven superconductor using a semiclassical U (1) lattice gauge theory. Specifically, we periodically drive the z -axis tunneling, which leads to an enhancement of the imaginary part of the z -axis conductivity at low frequencies if the driving frequency is blue-detuned from the plasma frequency. This has been proposed as a possible mechanism for light-enhanced interlayer transport in YBa2 C3 O7− δ (YBCO). In contrast to this enhancement of the conductivity, we find that the screening of magnetic fields is less effective than in equilibrium for blue-detuned driving, while it displays a tendency to be enhanced for red-detuned driving.